APPLYING INTRODUCTION, BODY, LANGUAGE STRATEGY TO ENRICH THE STUDENTS WRITING ABILITY - Adriani Jihad (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
The objective of this research is aimed to know the application of Introduction, Body, Language Strategy in improving students’ writing ability at the first-grade students of SMA YP PGRI 2 Makassar. This research used a pre-experimental method with one group pretest and posttest design. The population of this research was the first grade of SMA YP PGRI 2 Makassar. The total sample was 20 students. The result of the data showed that the mean score of post-tests was greater than the pre-test (85.15>56.2) and the t-test value was greater than the t-table value (2.339>1.729) at the level of significant 0.05. It can also prove that the result of the five components of writing, where the post-test result was higher than the pre-test. So, it can be concluded that from the score of the five components of writing on post-test (Content, vocabulary, language use, organization and mechanic) was greater than the score of the five components of writing on pre-test. So, it concluded that Introduction, Body, Language Strategy improves the students’ writing ability.